2000
DOI: 10.1306/012400701197
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Phosphorites from the Continental Margin Off Chennai, Southeast India: Analogs of Ancient Phosphate Stromatolites

Abstract: Pleistocene phosphorites occur on the continental margin off Chennai abundantly in the depth range of 186-293 m. They are associated with outer-shelf glauconites and carbonate skeletals including large shells of molluscs and rhodoliths. These are primary phosphate deposits and are similar to phosphate stratiform stromatolites. This is the first report of phosphate stratiform stromatolites during the Quaternary and modern times, and they provide a Quaternary analog for ancient phosphorites.Thin sections of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Monty (1976) suggested that the stratiform stromatolites with more or less planar laminae are synonymous with cryptalgal laminites. Phosphate stromatolites formed in shallow water settings during the Paleozoic (Bertrand-Sarfati et al 1997), Paleogene (Soudry and Panczer 1994) and Quaternary (Rao et al 2000) and in pelagic settings during Mesozoic along the northern margin of the Mediterranean Tethys (Krajewski et al 1981(Krajewski et al , 1994Follomi 1989;Martin-Algarra and Sanchez-Navas 1995) were reported. They suggested that the apatitic stromatolites tend to be composed of minute microlaminated units, which define both the structure and fabric of the authigenic phosphate deposit.…”
Section: Origin Of Cretaceous Phosphate Stromatolitesmentioning
confidence: 99%
See 4 more Smart Citations
“…Monty (1976) suggested that the stratiform stromatolites with more or less planar laminae are synonymous with cryptalgal laminites. Phosphate stromatolites formed in shallow water settings during the Paleozoic (Bertrand-Sarfati et al 1997), Paleogene (Soudry and Panczer 1994) and Quaternary (Rao et al 2000) and in pelagic settings during Mesozoic along the northern margin of the Mediterranean Tethys (Krajewski et al 1981(Krajewski et al , 1994Follomi 1989;Martin-Algarra and Sanchez-Navas 1995) were reported. They suggested that the apatitic stromatolites tend to be composed of minute microlaminated units, which define both the structure and fabric of the authigenic phosphate deposit.…”
Section: Origin Of Cretaceous Phosphate Stromatolitesmentioning
confidence: 99%
“…The microbial filaments and cell structures observed here are empty implying that phosphatization took place during their early stages of decay and before the complete decay of organic matter associated with the mats. The organic matter associated with mucillagenous sheaths of microbial filaments and cells may have (Vaz 1995;Rao et al 1998Rao et al , 2000Rao et al , 2002 Occurrences ( been the source of P and also acted as a substrate for phosphatization. The decaying bacteria associated with the microbial mats may have assimilated P and rapidly fixed P in their structures before getting destroyed.…”
Section: Sources Of P and Process Of Phosphatizationmentioning
confidence: 99%
See 3 more Smart Citations